Analisis Strategi Bisnis Mixue Cabang Sunan Giri : Studi Kasus Model dan Strategi Pemasaran Bisnis - Imelda Aprileny; Muhammad Ikhsan; Engkur Engkur; Muhammad Natser (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to analyze the business strategy of Mixue Sunan Giri Branch using the Business Model Canvas (BMC) and SWOT analysis within the context of implementing the marketing mix at the branch level. The research employed a descriptive qualitative case study approach. Data were collected through field observations, interviews, documentation, and literature review, and were analyzed qualitatively in accordance with the Student Creativity Program (PKM) format. The findings indicate that Mixue Sunan Giri Branch possesses several strengths, including strong brand awareness, competitive pricing, menu diversity that meets consumer preferences, and support from a standardized franchise system. However, the branch still faces challenges related to local promotional activities, product quality consistency, and human resource management at the operational level. Opportunities arise from the increasing public demand for ready-to-serve food and beverages and the growing use of digital media for marketing, while the primary threat comes from intense competition with similar brands in the surrounding area. Based on the analysis, the recommended strategies include strengthening community-based and digital marketing, improving product and service quality control, and enhancing employee competencies through continuous training. The implementation of these strategies is expected to improve competitiveness, maintain customer loyalty, and support the long-term sustainability of the franchise branch.